Structural changes in state-labour relations in South Africa, 1979-1995 : towards a framework for analysis - Thiel, Hermann P. E.(Hermann Paul Emil) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1996.